Determinación de la influencia de la aplicación de diferentes dosis de estiércol de ganado vacuno en la producción de compost a partir de cáscara de cacao - Ortiz Vargas, Maria Isabel (2015)
The cocoa husk represents the biggest product of the chocolate worldwide. Currently they have increased studies relating to this type of residues and its possible use, because these represent an important component of agricultura! residues and agro-industrial wastes in the world, these are a good source of renewable resources and energy. Internationally it has been developing possible uses of cocoa husk as a source of soils fertilizer, food for birds and animals, source of pectin and gums, elaboration of activated carbon and obtaining of dietary fiber. However in Peru is still being squandered and few studies about this. At the National University of San Martin - T, we see the necessity of carrying out an investigation that could exploit the presence ofnutrients in composting cocoa husk finding an organic fertilizer that has great ability to fertilize agricultura! soils. This research project was done with organic cocoa husk residues from farms of the Alto Mayo, in the San Martin regionwith the objective to determine the intluence of different doses of cow manure in the production of compost from husk cocoa (Theobroma cacao L.). Small rural farmers and agroindustries do not perform on composting and generate large quantities of organic residues in their production processes. Was sampled a certain amount of cocoa husk and experimenting was performed in biosolid composting windrows with different doses of cow manure to their respective chemical analysis in different process stages. The results showed that different doses of cow manure do not significantly intluence the production of compost from cocoa husks. Means that applying a dose of fresh manure of cattle that have available to decompose the residues that are generated in agricultura! fields, can take advantage ofthe microorganisms in the compost to accelerate the decomposition of cocoa husk and get compost it can be used as organic fertilizer in the same plantations. This activity enables incorporate good handling practices of residues that are generated on farms, making it more responsibly and sustainably. Keywords: cocoa, manure, compost, growing stimulus